If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -1) + -1(x + -1) = 6(x + 10) Reorder the terms: 3(-1 + 3x) + -1(x + -1) = 6(x + 10) (-1 * 3 + 3x * 3) + -1(x + -1) = 6(x + 10) (-3 + 9x) + -1(x + -1) = 6(x + 10) Reorder the terms: -3 + 9x + -1(-1 + x) = 6(x + 10) -3 + 9x + (-1 * -1 + x * -1) = 6(x + 10) -3 + 9x + (1 + -1x) = 6(x + 10) Reorder the terms: -3 + 1 + 9x + -1x = 6(x + 10) Combine like terms: -3 + 1 = -2 -2 + 9x + -1x = 6(x + 10) Combine like terms: 9x + -1x = 8x -2 + 8x = 6(x + 10) Reorder the terms: -2 + 8x = 6(10 + x) -2 + 8x = (10 * 6 + x * 6) -2 + 8x = (60 + 6x) Solving -2 + 8x = 60 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -2 + 8x + -6x = 60 + 6x + -6x Combine like terms: 8x + -6x = 2x -2 + 2x = 60 + 6x + -6x Combine like terms: 6x + -6x = 0 -2 + 2x = 60 + 0 -2 + 2x = 60 Add '2' to each side of the equation. -2 + 2 + 2x = 60 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 60 + 2 2x = 60 + 2 Combine like terms: 60 + 2 = 62 2x = 62 Divide each side by '2'. x = 31 Simplifying x = 31
| z^2+4z+16=0 | | -15-6x=3 | | 45x*45x+240x+180=0 | | 0.001*0.0001x=0.125 | | 3(3x-5)-2(4-3x)-4(1-2x)=5(3x-2) | | 10x-28=9 | | 0.35/x=12000 | | 3(2m-2)=12 | | 2pxX=4p^2 | | 35/x*100=12000 | | x*ln(x)-4=0 | | P=tan(px-y) | | xln(x)-4x=0 | | -7(3x+1)=7 | | 4(n+-4)=-6 | | 2(4x+6)=8 | | 2+4tanx=-1 | | 6x-2x+3x=42 | | 5(x+1)+2(x-3)=4 | | 3b+2=-35 | | 30x/9×2=5× | | 3(2x-1)=2.7 | | 10-(15-2x)=3(2x-7-2)(9-x) | | Xsquared+4x-12= | | 10-(15-2x)=3(2x-7-2)(9x-x) | | 2n+3n-10=20 | | 7a+1=5 | | 2(x_3)+x=3_2(x_8) | | 60+3x=3x | | 2x+7.99c=24 | | 3ln(14)+6ln(3)= | | X^2+5x-1500=0 |